Sistem Monitoring Penyewaan Alat-Alat Outdoor Berbasis Web - Aditya Nuryudha Iriandi; Iskandar Fitri; Sari Ningsih (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2022)
The purpose of this research is to make it easier to collect data to make it easier for business actors to monitor the rental of outdoor equipment. Applications built using HTML, CSS, and Java Script programming language systems then use the CodeIgniter framework and materialize components and use MySQL and XAMPP as databases and tools in running server-side. The waterfall method was chosen as a method in developing the system that was built. The results of the study found that; 1) The role of technology in the current digital era, can facilitate the handling of business management, especially in the field of equipment rental so that it helps problems and handling in processing and processing rental reports, 2) Hiking, Trekking, Mountaineering and so on customers will have a place to borrowing tools and climbing needs, and 3) By using the application that was built, it can make it easier to monitor the rental of outdoor equipment.